Influence of waxes on adhesion properties of bituminous binders. (1st February 2015) - Lamperti, Riccardo; Grenfell, James; Sangiorgi, Cesare; Lantieri, Claudio; Airey, Gordon D.
Highlights: Loss of adhesion represent one of the main causes of distress in asphalt pavements. We investigated the effects of two different waxes on bitumen–aggregate adhesion. The affinity was assessed by means of physico-chemical surface characteristics. Effects of wax and aggregates acidic/basic type are discussed. Independent evidences from rolling bottle tests well support the results. Abstract: The benefits at the base of WMA technologies are well established in the literature. They include the reduction in the energy consumption during the production of mixtures, the reduction in the emissions to the atmosphere in the production plant and a safer working environment. Although many studies have demonstrated good performance of this technology overall, some aspects are still unclear. This paper aims to investigate the effects of two different waxes, mixed with a 70/100 pen bitumen on bitumen–aggregate adhesion. Physico-chemical surface characteristics of three different aggregates were assessed and combined with those of the bitumens by means of the Dynamic Contact Angle and Dynamic Vapour Sorption Devices. These techniques are an alternative to the procedure used to visually assess the bitumen–aggregate affinity, as given in the in EN 12697-11 standard, in which the materials are mixed together and then immersed in water. Using these procedures the materials are not mixed together, but studied separately, and the evaluation of their affinity for one another is analytically expressed by means of the work of adhesion. Results have shown that waxes adversely affect the affinity of bitumen with aggregates by differing amounts, depending on the wax type and on the acidic/basic type of the aggregate.